Impact of the COVID-19 pandemic on antidepressant and antipsychotic use among children and adolescents: a population-based study - Antoniou, Tony; Pajer, Kathleen; Gardner, William; Penner, Melanie; Lunsky, Yona; Tadrous, Mina; Mamdani, Muhammad; Gozdyra, Peter; Juurlink, David N.; Gomes, Tara (Frontiers in Pediatrics, 2023)
The COVID-19 pandemic was associated with increases in the prevalence of depression, anxiety and behavioural problems among children and youth. Less well understood is the influence of the pandemic on antidepressant and antipsychotic use among children. This is important, as it is possible that antidepressants and antipsychotics were used as a 'stop-gap' measure to treat mental health symptoms when in-person access to outpatient services was disrupted. We examined trends in dispensing of these medications two years following the pandemic among children 18 years of age and under in Ontario, Canada. We conducted a population-based time-series study of antidepressant and antipsychotic medication dispensing to children and adolescents ≤ 18 years old between September 1, 2014, and March 31, 2022. We measured monthly population-adjusted rates of antidepressant and antipsychotics obtained from the IQVIA database. We used structural break analyses to identify the pandemic month(s) when changes in the dispensing of antidepressants and antipsychotics occurred. We used interrupted time series models to quantify changes in dispensing following the structural break and compare observed and expected use of these drugs. Results: Overall, we found higher-than-expected dispensing of antidepressants and antipsychotics in children and youth. Specifically, we observed an immediate decrease in antidepressant dispensing associated with a structural break in April 2020 (-55.8 units per 1000 individuals; 95% confidence intervals [CI] CI: -117.4 to 5.8), followed by an increased monthly trend in the rate of antidepressant dispensing of 13.0 units per 1000 individuals (95% CI: 10.2 to 15.9). Antidepressant dispensing was consistently greater than predicted from September 2020 onward. Antipsychotic dispensing increased immediately following a June 2020 structural break (26.4 units per 1000 individuals; 95% CI: 15.8 to 36.9) and did not change appreciably thereafter. Antipsychotic dispensing was higher than predicted at all time points from June 2020 onward. We found higher-than-expected dispensing of antidepressants and antipsychotics in children and youth. These increases were sustained through nearly two years of observation and are especially concerning in light of the potential for harm with the long-term use of antipsychotics in children. Further research is required to understand the clinical implications of these findings.